Towards the standardization of the absorbed dose report mode in high energy photon beams. (1st February 2021) - Younes, Tony; Chauvin, Maxime; Delbaere, Alexia; Labour, Joey; Fonteny, Victoria; Simon, Luc; Fares, Georges; Vieillevigne, Laure
Abstract: The benefits of using an algorithm that reports absorbed dose-to-medium have been jeopardized by the clinical experience and the experimental protocols that have mainly relied on absorbed dose-to-water. The aim of the present work was to investigate the physical aspects that govern the dosimetry in heterogeneous media using Monte Carlo method and to introduce a formalism for the experimental validation of absorbed dose-to-medium reporting algorithms. Particle fluence spectra computed within the sensitive volume of two simulated detectors (T31016 Pinpoint 3D ionization chamber and EBT3 radiochromic film) placed in different media (water, RW3, lung and bone) were compared to those in the undisturbed media for 6 MV photon beams. A heterogeneity correction factor that takes into account the difference between the detector perturbation in medium and under reference conditions as well as the stopping-power ratios was then derived for all media using cema calculations. Furthermore, the different conversion approaches and Eclipse treatment planning system algorithms were compared against the Monte Carlo absorbed dose reports. The detectors electron fluence perturbation in RW3 and lung media were close to that in water (≤1.5%). However, the perturbation was greater in bone (∼4%) and impacted the spectral shape. It was emphasized that detectors readings should be corrected by the heterogeneity correction factor that ranged from 0.932 in bone to 0.985 in lung. Significant discrepancies were observed between all the absorbed dose reports and conversions, especially in bone (exceeding 10%) and to a lesser extent in RW3. Given the ongoing advances in dose calculation algorithms, it is essential to standardize the absorbed dose report mode with absorbed dose-to-medium as a favoured choice. It was concluded that a retrospective conversion should be avoided and switching from absorbed dose-to-water to absorbed dose-to-medium reporting algorithm should be carried out by a direct comparison of both algorithms.